Wykonaj działania:
a) 2*[3(2a-b)²-(a+b)²-4[(2a+b)²-4(½a²b+1)]
b)-2/(9 ) x²+2(⅓ x-y)(⅓x+y)-5 [(x-y)2x-3x(x+⅙y)]
c) (a²- b²)²+(a²+b² )²- (√2 a²+ √(2 ) b²)(√2 a²- √2 b²)
d) (√2 x-1)(√2 x+1)- (√2 x-1)²+ (x-√2 )²
e) (√3ab- c)(√3ab+ c)- (√3ab- c)²+ (c- √3ab )²
Z GÓRY DZIĘKUJĘ:)

1

Odpowiedzi

2009-11-21T20:01:18+01:00
D) (√2x-1) (√2x+1)-(√2x-1)²+(x-√2)²=
(√2x)²-1²-(√2)²-2*√2*1 +1²+x²- 2*x*√2 + (√2)²=
2x²-1-2-2√2+1+x²-2√2+2= 3x²-4√2


(√3ab- c)(√3ab+ c)- (√3ab- c)²+ (c- √3ab )²
(√3ab)²-c² - (√3ab)²-2*√3ab*c+c² + c²-2*c*√3ab+(√3ab)²=
3a²b²-c²-3a²b²-2√3abc+c²+c²-2√3abc+3a²b²=
i tu juz redukcja :)

to jest proste tylko należy korzystać z wzorów skróconego mnożenia. :)